Efektivitas Peraturan Gurbenur Provinsi Nusa Tenggara Barat Nomor 51 Tahun 2020 Dalam Perlindungan Non-Aparatur Sipil Negara - Ida Bagus Gede Angga Juniarta (Universitas Pendidikan Nasional, 2022)
Currently, in the Province of West Nusa Tenggara (NTB) the Governor's Regulation Number 51 of 2020 concerning Obligations of Participation in the Employment Social Security Program has been issued. After the issuance of this regulation issued in 2020, in 2021 its implementation is still not visible. The research method used is an empirical legal research method using a descriptive approach. Efforts to improve welfare and ensure social security protection for all workers in the province of NTB, the local government has made several efforts to support the optimization of employment social security protection. However, looking at the current coverage, the protection is still not maximal, where the protection for Wage Recipient workers is 36.95% and Non-Wage Recipient workers is 1.24%. Article 5 paragraph (4) Governor's Regulation Number 51 of 2020 concerning Obligations of Participation in the Employment Social Security Program, that,